Effect of Obesity on Motor Functional Outcome of Rehabilitating Traumatic Brain Injury Patients. (August 2015) - Le, David; Shafi, Shahid; Gwirtz, Patricia; Bennett, Monica; Reeves, Rustin; Callender, Librada; Dunklin, Cynthia; Cleveland, Samantha
ABSTRACT: Objective: The aim of this study was to determine the association between obesity and functional motor outcome of patients undergoing inpatient rehabilitation after traumatic brain injury. Design: This retrospective study at an urban acute inpatient rehabilitation center screened data from 761 subjects in the Traumatic Brain Injury Model System who were admitted from January 2010 to September 2013. Inclusion criteria consisted of age of 18 years or older and an abnormal Functional Independence Measure motor score. Body mass index was used to determine obesity in the study population. Patients with a body mass index of 30.0 kg/m 2 or greater were considered obese. Results: A total of 372 subjects met the criteria for inclusion in the study. Of these, 54 (13.2%) were obese. Both obese and nonobese patients showed similar improvement in Functional Independence Measure motor score (mean [SD], 30.4 [12.8] for the obese patients, P = 0.115, and 27.3 [13.1] for the nonobese patients). The mean (SD) Functional Independence Measure motor scores at discharge for the obese and nonobese patients were 63.0 (12.6) and 62.3 (10.1) ( P = 0.6548), respectively. Conclusions: Obesity had no adverse impact on motor functional outcomes of the traumatic brain injury patients who underwent inpatient rehabilitation. Therefore, obesity should not be considered an obstacle in inpatient rehabilitation after traumatic brain injury, if patients are able to participate in necessary therapy.